Plant design for the manufacture of Terramycin-HC1 - Belo, Elias S.; Daracan, Godofredo M.; Reburiano, Manuel R. (Diliman, Quezon City College of Engineering, 1969)
This design project covers all aspects concerning the manufacture of Terramycin, a widely used antibiotic. The process employed is basically patterned after the Chas Pfizer plant in Sandwich, England whose plant license is to expire this year. Our yearly imports of Terramycin is continually increasing as shown in our economic survey. This is expected to increase some more as new uses are developed. This plant designed to produce 70 percent of our yearly import but room for expansion has been amply provided for to meet future demands. With an annual production of 100,000 pounds of Terramycin-HCl, the company needs an initial capital investment of P36,116,290.20. At a selling price of 68 dollars per pound, the expected gross sales is P43,748,208.00. The net income (after taxes) of the company will be P17,547,581.94 giving them a rate of return on investment of 48.7 percent. At this income, the pay-out time is 1.71 years. Based on the above findings, the establishment of a Terramycin plant in the Philippines is highly recommended.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Drug factories; Oxytetracycline